HIDRAdisk: validation of an innovative visual tool to assess the burden of hidradenitis suppurativa. (5th March 2019) - Peris, K.; Lo Schiavo, A.; Fabbrocini, G.; Dini, V.; Patrizi, A.; Fusano, M.; Bianchi, L.; Guanziroli, E.; Guarneri, C.; Parodi, A.; Bertoldi, A.; Musumeci, M.L.; et al.
Abstract: Background: Hidradenitis suppurativa (HS) is a chronic, relapsing, inflammatory skin disease characterized by painful inflamed nodules, recurrent abscesses and fistulas located in apocrine gland–bearing body sites. The negative impact of HS on patient's quality of life (QoL) has been reported to be greater than other dermatologic conditions as psoriasis and atopic eczema, and its improvement is an important goal in disease management. Nowadays, there are no specific validated QoL instruments available for HS and generic dermatologic questionnaires are used. Objective: The objective of this study was to demonstrate the validity, reliability and responsiveness of HIDRAdisk, a new innovative tool designed for rapid assessment of HS burden and, at the same time, an intuitive graphic visualization of the measurement outcome. Methods: A multicentre, longitudinal, observational study was conducted to validate the HIDRAdisk compared with other validated questionnaires [Skindex‐16, Dermatology Life Quality Index (DLQI), Work Productivity and Activity Impairment–General Health (WPAI:GH)] and to evaluate its correlation with disease severity in Italian patients with any degree of HS severity, as measured by Hurley stage and HS Physician Global Assessment (HS‐PGA). Results: A total of 140 patients (59% women; mean age 34.9 ± 11.0 years) were enrolled in 27 dermatologic centres. HIDRAdisk showed a strong correlation with Skindex‐16 and DLQI, and a good one with WPAI:GH (correlation coefficient: 0.7568, 0.6651 and 0.5947, respectively) and a statistically significant correlation with both Hurley stage and HS‐PGA. Very good internal consistency (Cronbach coefficient >0.80; intraclass correlation coefficient >0.6), with correlation between the 10 items, good test–retest reliability (Spearman correlation coefficient, 0.8331; P < 0.0001) and responsiveness to changes were demonstrated. Conclusion: Our study shows that HIDRAdisk, a short and innovative visual HS QoL instrument, has been psychometrically validated in Italian language and it may help improve the management of HS once implemented in routine clinical practice.